Urban and modern: theoretical considerations - Aranda Dioses, Edith (2018)
This article approaches the analysis of the relationship between the concepts of «urban» and «modern», incorporating some conceptual precisions about the components of this relationship. We address the historical scenario to explain the role that the city has had as an institutional space in modernity. From this referential context, a reflection is made about the modern city in Latin America and Peru to try and unravel its particularities in the composition of societies such as ours. The theoretical framework we develop recovers the contributions from diverse authors, who from different perspectives, study the modern city.